Dysbiosis and Restoration Dynamics of the Gut Microbiome Following Therapeutic Exposure to Florfenicol in Snubnose Pompano (Trachinotus blochii) to Aid in Sustainable Aquaculture Production Strategies - Sumithra, T. G.; Sharma, Krupesha S. R.; Gangadharan, Suja; Suresh, Gayathri; Prasad, Vishnu; Amala, P. V.; Sayooj, P.; Gop, Ambarish P.; Anil, M. K.; Patil, Prasanna Kumar; Achamveetil, Gopalakrishnan (Frontiers in Microbiology, 2022)
Information on unintended effects of therapeutic exposure of antibiotics on the fish gut microbiome is a vital prerequisite for ensuring fish and environmental health during sustainable aquaculture production strategies. The present study forms the first report on the impact of florfenicol (FFC), a recommended antibiotic for aquaculture, on the gut microbiome of snubnose pompano (Trachinotus blochii), a high-value marine aquaculture candidate. Both culture-dependent and independent techniques were applied to identify the possible dysbiosis and restoration dynamics, pointing out the probable risks to the host and environment health. The results revealed the critical transient dysbiotic events in the taxonomic and functional metagenomic profiles and significant reductions in the bacterial load and diversity measures. More importantly, there was a complete restoration of gut microbiome density, diversity, functional metagenomic profiles, and taxonomic composition (up to class level) within 10–15 days of antibiotic withdrawal, establishing the required period for applying proper management measures to ensure animal and environment health, following FFC treatment. The observed transient increase in the relative abundance of opportunistic pathogens suggested the need to apply proper stress management measures and probiotics during the period. Simultaneously, the results demonstrated the inhibitory potential of FFC against marine pathogens (vibrios) and ampicillin-resistant microbes. The study pointed out the possible microbial signatures of stress in fish and possible probiotic microbes (Serratia sp., Methanobrevibacter sp., Acinetobacter sp., and Bacillus sp.) that can be explored to design fish health improvisation strategies. Strikingly, the therapeutic exposure of FFC neither caused any irreversible increase in antibiotic resistance nor promoted the FFC resistant microbes in the gut. The significant transient increase in the numbers of kanamycin-resistant bacteria and abundance of two multidrug resistance encoding genes (K03327 and K03585) in the treated fish gut during the initial 10 days post-withdrawal suggested the need for implementing proper aquaculture effluent processing measures during the period, thus, helps to reduce the spillover of antibiotic-resistant microbes from the gut of the treated fish to the environment. In brief, the paper generates interesting and first-hand insights on the implications of FFC treatment in the gut microbiome of a marine aquaculture candidate targeting its safe and efficient application in unavoidable circumstances. Implementation of mitigation strategies against the identified risks during the initial 15 days of withdrawal period is warranted to ensure cleaner and sustainable aquaculture production from aquatic animal and ecosystem health perspectives.